Structure and dielectric properties of Bi0.5K 0.5TiO3-SrTiO3 lead-free ceramics - Ruangphanit, Anucha; Phetnoi, Prapapim; Niemcharoen, Surasak; Muanghlua, Rangson (My University, 2011)
Bismuth potassium titanate - strontium titanate (1-x)Bi0.5K 0.5TiO3-(x)SrTiO3 (BKT-ST) lead-free ceramics when x = 0-0.20 were synthesized by the solid state reaction method with normal sintering. The ferroelectric phase transition was studied by X-ray diffraction (XRD). All compositions showed a single phase perovskite structure with tetragonal symmetry at room temperature and the phase structure transformed from ferroelectric tetragonal - paraelectric cubic in the range of x ≥ 0.10. Dielectric study revealed that the dielectric relaxor behavior was induced with increasing ST and transition temperature (Tm εr max) of ST-doped BKT had a tendency to decrease with increasing ST. The Bi 0.5K0.5TiO3-SrTiO3 system was expected to be a new and promising candidate for lead-free capacitors. © (2011) Trans Tech Publications.
Keywords: Dielectric properties; Lead-free ceramics